Investigating the Effect of Solanum lycopersicum L. (Tomato) Pomace on Growth Performance and some Blood Indices of Broiler Chickens by Meta-Analysis Method - Zahra Sahragard; seyyed javad Hosseini-vashan; Hossein Naeemipour Younesi; Seyyed Homayon Farhangfar (پژوهشهای علوم دامی ایران)
Introduction: Tomato is a valuable vegetable that is rich in vitamins such as vitamin A, E, C, B and K, and also some of minerals such as phosphorus, iron, calcium, which are important for metabolic activities. Tomato pomace is a byproduct that produce in the tomato paste production. The composition of tomato pomace in terms of percentage of crude protein, crude fat, lycopene, beta-carotene, ascorbic acid, alpha-tocopherol, lycopene and beta-carotene are: 11%, 4.5%, 0.8 mg, 13. 0 mg, 1.73 mg, 0.07 mg and 281 and 24.3 mg per kg of dry matter respectively. The antioxidant capacity of tomato pomace is related to the substances in it, especially lycopene, which reduces the effect of reactive oxygen species and the destructive effects of these compounds on the cell membrane and mitochondrial structure. Tomato pomace has a high fiber content, which may have undesirable effects on broiler performance. This meta-analysis is a systematic review based on previous studies. The aim of this meta-analysis was to examine the effects of tomato pomace on growth performance and selected blood indices in broiler chickens.Material and Methods: In order to collect the required information, a comprehensive search was conducted among articles and thesis through Persian and Latin databases using keywords, tomato pomace, carcass efficiency, cholesterol, heterogeneity test. Studies (available data) in the field of using tomato pomace in Farsi and English were collected and categorized. The search was done in various databases, including PubMed, ISI Web of Science, Irandoc, etc. In the next step, the most frequently reported data from the reviewed articles that aligned with the research objectives were selected. The study area was refined by identifying the influencing factors and attributes relevant to the meta-analysis. The data were then coded, and after an initial review and removal of duplicates, a total of 12 studies were included in this meta-analysis. Among these, 9 comparisons were conducted for feed conversion ratio, 10 for feed consumption and body weight gain, and 4 for carcass characteristics and efficiency. Additionally, comparisons were made for the percentages of heart and liver, blood lipid levels, blood glucose levels, and total protein concentrations. Then the statistical analysis of the data was done in the CMI (CMA) software. Both fixed and random effects models were used to combine the effect size. To evaluate the publication basis, funnel plot and statistical tests on Tomato pomace were used.Results and Discussion: The abdominal fat percentage (-0.354±1.44), heart percentage (-0.353±0.294), pancreas percentage (-0.504± 0.316), gall bladder percentage (-0.027± 0.961), glucose (-0.091± 0.331), LDL (-1.942±0.644), total protein (-1.505± 0.003), cholesterol concentration (-0.290±0.04), feed intake in starter (0.072± 0.531) were lowered when tomato pomace were added to the broiler diet. The effect of inclusion of tomato pomace on weight gain during the growth period, feed intake in all periods and FCR in the starter, grower, and finisher period, the blood concentration of triglyceride, glucose, and the percentage of abdominal fat, liver, heart, pancreas and gall bladder, also breast was not significantly affected by tomato pomace. Some researcher also reported that inclusion of tomato pomace to broiler diet did not effect on broiler performance however in the high levels of tomato pomace in broiler diet observed undesirable effects. Tomato pomace has some bioactive components such as alpha-tocopherol, lycopene, phenolic, organic acids, essential fatty acids, amino acid and vitamins. However, there is a higher concentration of crude fiber in tomato pomace.Conclusion: Therefore, the findings of the present study show that application of tomato pomace has a significant effect on weight gain in the starter, total and finisher periods, FCR in the total and finisher period, total protein, cholesterol, HDL, LDL concentration. It is recommended that tomato pomace can be replaced the part to broiler diet.